Competitive advantage through information technology innovation adoption by small and medium enterprises in Malaysia - Moghavvemi, S.; Hakimian, F.; Rahmatullah, A.H.; Kaur, A.; Tengku Feissal, T.M.F. (2011)
The Information Technology concept is considered as a powerful competitive weapon in the modern economy. This paper seeks to explain the impact of information technology innovation on a competitive advantage; the barriers and the benefits companies gain from adopting and using these innovations. This study used IDT as the base theory, and added attitude and self efficacy as determinants to measure individual‟s perception toward innovation adoption. Individual self-efficacy and attitude toward innovation adoption shape beliefs and perceptions toward innovation, leading them to adopt or reject an innovation. Adding these factors to IDT will examine the individual‟s dimension toward technology adoption. This research reviews the role of SMEs in Malaysian economy and the effect of government policy in encouraging companies to adopt IT innovation. This is an ongoing research, and at this stage, we are mainly developing a theoretical argument and methodology that is currently in the process of being tested.